Pertussis immunisation and atopic outcomes - Perez Chacon, Gladymar (Curtin University, 2022)
The studies in this thesis aimed to examine the potential effects of a heterologous (mixed) whole-cell/acellular pertussis vaccine schedule versus the standard acellular-only vaccine schedule on atopic outcomes. The results presented here support the safety and immunogenicity of the mixed pertussis vaccine schedule and therefore the conduct of the second stage of the OPTIMUM clinical trial, which will examine the efficacy of the mixed schedule for preventing IgE-mediated food allergy by 12 months